2017
DOI: 10.1080/02699052.2017.1366551
|View full text |Cite
|
Sign up to set email alerts
|

Does the fear avoidance model explain persistent symptoms after traumatic brain injury?

Abstract: Background: A minority of patients with mild traumatic brain injury (mTBI) experience a persistent symptom complex also known as post-concussion syndrome. Explanations for this syndrome are still lacking. Objective: To investigate if the fear avoidance model, including catastrophizing thoughts and fear avoidance behaviour, poses a possible biopsychosocial explanation for lingering symptoms and delay in recovery after traumatic brain injury (TBI) with special focus on mTBI. Design: Cross-sectional study. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 64 publications
3
75
2
Order By: Relevance
“…Therefore, it is difficult to accept that post-concussion symptoms cohere as a syndrome because they share a single latent underlying cause, such as brain damage or a mental disorder. Multiple social psychological factors, such as expectations and misattributions (47, 6771), “good-old-days” bias (47, 7379), perceived injustice (87), fear avoidance (81, 82), socio-environmental factors such as compensation seeking (164166), vulnerability factors such as pre-injury mental health problems (21, 36, 109111), and neurological factors, such as microstructural changes to white matter (167), have been shown to be associated with persistent post-concussion symptoms. However, none have emerged as a latent common cause, and most in the field accept that post-concussion symptoms are multifactorial in causation.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is difficult to accept that post-concussion symptoms cohere as a syndrome because they share a single latent underlying cause, such as brain damage or a mental disorder. Multiple social psychological factors, such as expectations and misattributions (47, 6771), “good-old-days” bias (47, 7379), perceived injustice (87), fear avoidance (81, 82), socio-environmental factors such as compensation seeking (164166), vulnerability factors such as pre-injury mental health problems (21, 36, 109111), and neurological factors, such as microstructural changes to white matter (167), have been shown to be associated with persistent post-concussion symptoms. However, none have emerged as a latent common cause, and most in the field accept that post-concussion symptoms are multifactorial in causation.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
“…They are also common in people seen for psychological treatment (52), outpatients seen for minor medical problems (53), personal injury claimants (53, 54), and people with post-traumatic stress disorder (PTSD) (55), orthopedic injuries (11), chronic pain (42, 5659), whiplash (60), anxiety (61, 62), and depression (63). Biopsychosocial conceptualizations of the symptoms and syndrome (6466) emphasize a diverse range of personality and social psychological factors that contribute to how symptoms are perceived, experienced, and reported, such as expectations and misattributions (47, 6771), coping and illness perceptions (72), “good-old-days” bias (47, 7379), cognitive hypochondriasis (80), fear avoidance (81, 82) cogniphobia (83, 84), nocebo effect (85, 86), perceived injustice (87), iatrogenesis (17, 27), resilience (88, 89), Type D personality (90, 91), and other personality characteristics, particularly compulsive, histrionic, dependent, and narcissistic traits (21, 61). A multidimensional model for conceptualizing the post-concussion syndrome suggests that setbacks in several aspects of a person's life (physical, emotional, cognitive, psychosocial, vocational, financial, and recreational) serve as cumulative stressors that interact with personality and pre-morbid physical and mental health factors, resulting in the syndrome (21, 92, 93).…”
Section: Introductionmentioning
confidence: 99%
“…Total scores range from 0 to 64 with higher scores indicating a higher frequency and severity. Three or more symptoms, indicated by at least three items with an item score of 2 or higher, were used as a criterion for a disabling symptom complex (Wijenberg et al, 2017). This questionnaire was adapted for use within the healthy population as suggested by Dean et al (2012).…”
Section: Self-report Measuresmentioning
confidence: 99%
“…The model has been adapted and applied to various complaints in different patient populations (Cima et al, 2012;Wijenberg et al, 2020;Vlaeyen et al, 2016;Wijenberg et al, 2016), including patients who experienced mild injury with cognitive deficits as a consequence, such as post-concussion symptoms following mTBI (Wijenberg et al, 2020;Wijenberg et al, 2017). Numerous studies confirmed the potential of this adapted model in explaining the disease process leading from early benign symptoms to persistent symptoms in patients with mTBI (Wijenberg et al, 2020;Silverberg et al, 2019Silverberg et al, , 2018Snell et al, 2020;Wijenberg et al, 2017). Although this adapted model has not yet been tested in healthy adults, the original fear-avoidance model (assessing pain) was tested and validated in healthy adults across several studies (Houben et al, 2005;Sullivan et al, 1995;Trost et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation